1981
DOI: 10.1111/j.1432-1033.1981.tb05331.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Esterase 1F, the Albumin Esterase of the House Mouse (Mus musculus)

Abstract: Esterase 1 F was isolated from mouse serum and purified by ion-exchange chromatography, isoelectrofocusing, and molecular sieve chromatography. It is considered to be a glycoprotein with an apparent molecular weight of 75000. The equivalent weight (= 77000 x g/mol) was estimated by titration of the catalytic site with diethyl p-nitrophenyl phosphate. The Michaelis constant K , and the catalytic constant k,,, of the enzyme for 4-nitrophenyl hexanoate were determined. Esterase I F is characterized by its ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
4

Year Published

1981
1981
1998
1998

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 25 publications
0
13
0
4
Order By: Relevance
“…5 ) which have previously been shown to be immunologically related [ 5 ] . However, esterase 6A does not cross-react with serum raised against esterase 2B (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 ) which have previously been shown to be immunologically related [ 5 ] . However, esterase 6A does not cross-react with serum raised against esterase 2B (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, esterase 6A does not cross-react with serum raised against esterase 2B (Fig. 5 ) ; similarly neither esterase 1F nor esterase 9A precipitate with serum raised against esterase 2B [5]. All foul-esterases are coded for by the so-called esterase region [2Y] on chroniosome 8 and the gene for esterase 6 was located between the genes for esterases 1 and 2 [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1. 1) from animal sources have been carried out, and it has been reported that plural esterases are present in liver/,2) serum 3 ) or other tissues,4,S) as so-called isoenzymes. Recently, characterization of individualesterases belonging to isoenzymes from animal sources has been attempted, to clarify the mechanism of formation of complicated isoenzymes.…”
mentioning
confidence: 99%